‘Bisexuality’ in the Origins of Psychoanalysis - Janaína Namba (Critical Hermeneutics)
Many authors have examined texts by Freud that belong to the “prehistory” of psychoanalysis. They deal with anatomy, physiology and neuropathology and date from the period from 1876 to 1886. In this article we examine some of these texts and point to some consequences of the study of this beginning of Freudian psychoanalytic thought.